MORPHOLOGICAL CHARACTERISTICS AND CALCIFICATION DEGREES OF THE 4th TO 8th COSTAL CARTILAGES ON NON-CONTRAST COMPUTED TOMOGRAPHY (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the morphological characteristics and degree of calcification of the 4th to 8th costal cartilages on non-contrast CT scans images.Materials and methods: A cross-sectional descriptive study with comparative analysis was conducted on 103 patients who underwent non-contrast CT scans including the costal cartilage region at Medic Medical Center, Ho Chi Minh City, from December 2025 to February 2026.Results: Among 103 patients, corresponding to 1030 costal cartilages examined, females accounted for the majority (69.9%), with a mean age of 31.5 ± 8.3 years. The prevalence of costal cartilage calcification was 51.9%. Peripheral calcification was the predominant pattern (20.4-38.8%), while central calcification was the least common. Most costal cartilages showed no calcification or only mild calcification (grade 0 and grade 1 accounted for 89.1%). Both the prevalence and severity of calcification increased proportionally with age, with the highest frequency observed in the 44-56 age group. The 4th and 5th costal cartilages demonstrated the most pronounced changes over time.Conclusion: Chest CT scans help accurately determine the morphological characteristics and degree of costal cartilage calcification, allowing for personalized selection of the optimal location and timing for costal cartilage harvesting for each patient.
Keywords: Costal cartilage calcification, costal cartilage, computed tomography.